Qualitative Analysis and Periodic Cusp Waves to a Class of Generalized Short Pulse Equations (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we qualitatively study periodic cusp waves to a class of generalized short pulse equations, which are of the general form of three special generalized short pulse equations, from the perspective of dynamical systems. We show the existence of smooth periodic waves, periodic cusp wave and compactons, obtain exact expression of periodic cusp wave and illustrate the limiting process of periodic cusp wave from smooth periodic waves.